1997
DOI: 10.1002/art.1780400712
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aging on human chondrocyte responses to transforming growth factor β. Increased pyrophosphate production and decreased cell proliferation

Abstract: Objective. To address the influence of age on inorganic pyrophosphate (PPi) accumulation in human articular chondrocytes.Methods. Articular cartilage was obtained from men and women in 2 different age groups: ages 15-55 and 56-91. The effects of transforming growth factor Pl (TGFP1) on PPi levels in the media and cell lysates of chondrocytes were investigated. In addition, the effects of TGFP on PPi accumulation were compared with chondrocyte proliferation.Results. TGFPl increased PPi levels to a greater exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…14 In addition to its effect on osteophytosis, transforming growth factor β1 enhances production of extracellular pyrophosphate by chondrocytes, 30 and mechanical perturbation of chondrocytes increases the release of ATP, a potent source of extracellular pyrophosphate, 31 thereby predisposing to pyrophosphate crystal formation. Such shared chemical and/or mechanical predisposing factors may explain the association between osteophytosis and chondrocalcinosis seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition to its effect on osteophytosis, transforming growth factor β1 enhances production of extracellular pyrophosphate by chondrocytes, 30 and mechanical perturbation of chondrocytes increases the release of ATP, a potent source of extracellular pyrophosphate, 31 thereby predisposing to pyrophosphate crystal formation. Such shared chemical and/or mechanical predisposing factors may explain the association between osteophytosis and chondrocalcinosis seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Important changes occur in chondrocyte production of pyrophosphate with aging. The levels of constitu- tively produced and TGF-␤-induced pyrophosphate increase with aging in articular chondrocytes (31,32). Thus, with advancing age there are several changes that represent potential risk factors for the development of osteoarthritis.…”
Section: Fig 3 (A) Ntpph and Alkaline Phosphatase Activity Apoptotmentioning
confidence: 99%
“…Characterization of human [2,13], equine [21], bovine [1,7,11,35], rabbit [34] and mouse [25] cultured articular cartilage explants revealed that intrinsic metabolism of chondrocytes and their response to external factors vary with animal age. It has also been shown that chondrocytes isolated from cartilage behave in an age-dependent manner, although many of these studies involved monolayer culture [8,27,29,32,33], which induces dedifferentiation of chondrocytes towards a more fibroblastic-like phenotype.…”
Section: Introductionmentioning
confidence: 99%